Thiosulfate as an alternative lixiviant to cyanide for gold ores - Aylmore, Mark (Elsevier, 2016)
Thiosulfate is generally considered to be an attractive alternative reagent to cyanide for processing gold. It is relatively inexpensive and nontoxic, forms strong gold and silver complexes, and readily leaches gold ores when catalyzed by Cu(II). Research over the past 30 years has focused mostly on the understanding and applying the copper-catalyzed ammoniacal thiosulfate system to carbonaceous ores and copper–gold ores where gold recovery is poor when using cyanide or where cyanide consumption is high. Researchers have also investigated ammonia-free and alternative oxidant systems to mitigate environmental issues associated with the use of ammonia. Barrick Gold Corporation developed and commercialized a copper-calcium thiosulfate process, which is currently in use at Goldstrike, Nevada, USA. This chapter reviews recent advances in understanding of the chemistry and mechanism of gold dissolution, influence of mineralogy, certain cations and anions, as well as gold recovery options. The speciation and stability of the thiosulfate system are considered under typical leaching conditions, together with examples of leaching various gold ores that have been reported in the literature. Further work by the industry is required to continue developing robust overall process flow sheets incorporating gold recovery, reagent recycling, and impurity control for a wider range of ore applications.